Land Use Change and Socio-Economic Evaluation in S\~ao Jorge Island (Between 15th and 20th Century) - Tomaz Dentinho; Vanda Serpa; Paulo Silveira; Joana Goncalves (European Regional Science Association (ERSA), 2006)
The agenda explain the historical evolution of land uses in S\~ao Jorge Island (Azores- Portugal) between 15th-20th century.The economic exploitation of the island space prosecuted itself in simultaneous with his colony, one form to guarantee the auto supplying of the populations. First we assess the capacity of the island territory for different uses based on agronomic analysis and transform these capacities in attractiveness coefficients.Then we design a spatial interaction model with five different sectors which employment can be closely related with surface area, first to five zones in the island and within those zones to small plots of 1 hectare each.Finally we use historical data on population and main export crops in order to calibrate the model for each century. Therefore, based on data on the export crop and on the population it is possible to estimate the different land use of the island for all the sectors and to assess the carrying capacity of the island.
Keywords: 330